Effect Of Cooling Medium And Tempering On Microstructures And Hardness Of SK3 High Carbon Steel - Jumaidin, Ridhwan; Abdullah, Muhammad Ilman Hakimi Chua; Jopri, Iffa Marina; Hussin, Mohamed Saiful Firdaus; Hasan, Rafidah; Saleman, Abdul Rafeq; Idral, Febrian; Aziz, Alia Ruzana (Penerbit Akademia Baru, 2019)
This paper presents a study on the effect of heat treatments i. e annealing, quenching, normalizing, and tempering on the characteristics of SK3 high carbon steel. The specimens were heated to austenitizing temperatures at 760C, 840C, 920C, 1000C and 1080°C, before cooled by using different cooling medium i.e. oil quenching, air cooling, and furnace cooling. Tempering process was conducted on the quenched specimen by reheating at 500°C and cooled to room temperature. Material characterization techniques such as hardness test and morphological investigation were carried out for all specimens. The heat treatment has significantly improved the hardness of the material. The quenched specimen (rapid cooling) shows the highest increment of hardness by 709%. This was followed by the normalized specimen (moderate cooling) and annealed specimen (slow cooling) which shows 425% and 170% of increment respectively. However, tempering treatment on the quenched specimen has shown a slight decrease in the hardness value. In terms of microstructure, the annealed specimen produced coarse grain size while the quenched specimen produced a fine grain size. The hardness of the specimen subjected to tempering process is lower than that of quenching process.